2019
DOI: 10.3390/cells9010019
|View full text |Cite
|
Sign up to set email alerts
|

Serine-Arginine Protein Kinase 1 (SRPK1) as a Prognostic Factor and Potential Therapeutic Target in Cancer: Current Evidence and Future Perspectives

Abstract: Cancer, a heterogeneous disease composed of tumor cells and microenvironment, is driven by deregulated processes such as increased proliferation, invasion, metastasis, angiogenesis, and evasion of apoptosis. Alternative splicing, a mechanism led by splicing factors, is implicated in carcinogenesis by affecting any of the processes above. Accumulating evidence suggests that serine-arginine protein kinase 1 (SRPK1), an enzyme that phosphorylates splicing factors rich in serine/arginine domains, has a prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 93 publications
0
26
0
3
Order By: Relevance
“…The drug, SCO-101, binds to ABCG2 and leads to its degradation. It also inhibits the function of the SRPK-1 kinase which has been suggested to be involved in drug resistance [30]. SCO-101 was in four clinical phase I studies shown to be a safe oral drug with only limited toxicity [31].…”
Section: Discussionmentioning
confidence: 99%
“…The drug, SCO-101, binds to ABCG2 and leads to its degradation. It also inhibits the function of the SRPK-1 kinase which has been suggested to be involved in drug resistance [30]. SCO-101 was in four clinical phase I studies shown to be a safe oral drug with only limited toxicity [31].…”
Section: Discussionmentioning
confidence: 99%
“…Because of their multiple activities, aberrant expression and/or activity of all these kinases have been frequently associated to cancer development. For studies regarding the role of these kinases in cancer, we refer the interested readers to dedicated reviews and references therein ( Czubaty and Piekielko-Witkowska, 2017 ; Nikas et al, 2019 ; Laham et al, 2020 ).…”
Section: Cellular Functions and Regulatory Mechanisms Of Cmgc Kinasesmentioning
confidence: 99%
“…Similarly, the inhibition of SRPK1 could simultaneously influence a variety of oncogenic processes, including angiogenesis, apoptosis, proliferation, migration, invasion, and metastasis. Interestingly, targeting SRPK1 could enhance sensitivity to platinum-based chemotherapy in certain carcinomas [96] . Splicing-correcting therapy uses splice-switching oligonucleotides (SSOs) to target splicing defects, which are often used to treat neuromuscular disorders in clinical practice [97] .…”
Section: Therapeutic Strategy Of Targeting Alternative Splicing Procementioning
confidence: 99%